A SUCCESSFUL STRATEGY OF POLITICAL PARTY CAMPAIGN AHEAD OF ELECTION IN DEVELOPED COUNTRIES - Linayati Lestari; Askarmin Harun; Amrullah Rasal; Ronald Parlindungan; Fajarina Nur Fatiha; Susanto Susanto (JURNAL DIMENSI, 2023)
This study aims to analyze the arts performed by political parties before the democratic era of disruption. Information and communication technology development has forced political parties to be enthusiastic about using the internet, including social media. The internet and social media are inseparable; social media is a nomenclature of the communication art of political parties that goes according to their wishes. This study uses a qualitative data analysis software approach (QDAS) and bibliometrics with the help of VosViewer and Nvivo 12 software. The research data sources use 428 articles from the Scopus database. The data search phase uses the keywords "Communications" and "Political Parties" from 2015-2021. The analysis results show that the arts performed by pre-democratic political parties are candidate, election, campaign, Facebook, Twitter, and Instagram, being the main keywords that appear. The findings of this study are the art of pre-democratic political communication; social media is the pre-eminent platform used by political parties. Currently, Facebook, Twitter, Youtube, and Instagram are the dominant platforms seen being used by political parties in conducting campaigns ahead of the general election. Utilizing social media is the advantage of each political party, aiming to get wider coverage and fast response at every level of society.